Learning processing a beginner's guide to programming images, animation, and interaction - Shiffman, Daniel (Elsevier/Morgan Kaufmann, 2015)
This book teaches you the basic building blocks of programming needed to create cutting-edge graphics applications including interactive art, live video processing, and data visualization. A unique lab-style manual, the book gives graphic and web designers, artists, and illustrators of all stripes a jumpstart on working with the Processing programming environment by providing instruction on the basic principles of the language, followed by careful explanations of select advanced techniques. Within these pages, ITP (Tisch School of the Arts, New York University) professor Daniel Shiffman demonstrates the fundamentals of programming that will expand your understanding of what is possible in the world of computer graphics. By travelling beyond the confines of proprietary software, you will be empowered to create your own custom design tools ... Source code and supplemental tutorials are also available through an online companion site.